Investment attractiveness of the real sector of the economy in the framework of sustainable development - O. E. Astafieva (Publishing House of the State University of Management, 2021)
The article discusses the main problems associated with the development and implementation of investment projects at enterprises of the real sector of the economy for sustainable development. The current situation in the investment and construction sector of the economy has been evaluated and the ways of solving the main problems of investment activity in the construction industry are outlined. The issues of formation mechanism of the investment attractiveness of industries and individual organizations, production and investment activities have been consistently considered. Traditional indicators and criteria of investment efficiency have been analysed. The expediency of using indicators of the return on capital or assets of the organization necessary for the implementation of the project has been substantiated. It has been noted that in the process of developing an organization’s sustainable development strategy, it is necessary to take into account its digital transformation, within the framework of the possibility of functioning in a single digital environment in order to increase competitiveness. The applying a comprehensive assessment of the effectiveness of attracting investments for the implementation of investment programs based on the selected criteria, taking into account their functioning in the digital environment, – has been recommended.